Cobalamin Co‐Limits Phytoplankton and Bacterial Biomass and Activity in Eastern Mediterranean Coastal Waters. Issue 23 (12th December 2022) - Rahav, Eyal; Silverman, Jacob
Abstract: In this study, we examined the response of phytoplankton and heterotrophic bacteria to B12 amendments in microcosm experiments in the coastal southeastern Mediterranean Sea (SEMS) during the summer, where ambient levels of dissolved B12 ranged from as low as ∼2 pmol L −1 to 60 pmol L −1 (median 5.3 pmol L −1 ). Additions of B12 (20 pmol L −1 ) to surface seawater triggered a 4‐fold increase in NO3 +NO2 uptake compared to unamended seawater, resulting in proliferation of mainly pico/nano‐eukaryotic phytoplankton (∼30%) and increase in primary and bacterial productivity (40%–50%). Complimentary experiments that tested the combined effects of nutrient (NO3 and PO4 ) and B12 additions suggest that phytoplankton were primarily NO3 and B12 co‐limited, whereas heterotrophic bacteria were PO4 and B12 co‐limited. These results provide valuable information about the marine distribution of nutrient limitation in low nutrients low chlorophyll (LNLC) environments such as the SEMS, and how bacterioplankton might respond to environmental perturbations. Plain Language Summary: Most biogeochemical studies have focused primarily on the effects of dissolved nitrate and orthophosphate on marine phytoplankton and bacterial productivity. However, vitamin B12 is also an important co‐factor for phytoplankton and bacteria, which has been far less investigated. These few studies showed that despite the very low concentrations of dissolved B12 in the marine environment, it has a strong influence on phytoplankton and bacterial productivity. Here, we followed phytoplankton and bacterial abundance and activity in response to B12 additions using high‐resolution daily measurements, and microcosm bioassays with additional nutrient simulations (nitrate, orthophosphate). Our study site was the coastal southeastern Mediterranean Sea, and the experiments were done during the summer when the most nutrient‐poor conditions prevail. Our results indicate that additions of B12 triggered a rapid increase in nitrate uptake, resulting in increased abundance of phytoplankton (mostly pico/nano‐eukaryotes) and photosynthesis rates. We also show that phytoplankton "need" both nitrate and vitamin B12 to proliferate, while bacteria require orthophosphate and B12 to support their growth. These results add to the current knowledge on the limitations of phytoplankton and bacteria in the coastal southeastern Mediterranean Sea and have implications for the whole coastal food‐web in this nutrient‐poor ecosystem. Key Points: Addition of B12 increased pico/nano‐eukaryotes abundance during the illuminated hours and of cyanobacteria during night‐time B12 amendments accelerated NO3 uptake by phytoplankton, resulting in increased primary production rates Phytoplankton were co‐limited by NO3 and B12 while heterotrophic bacteria were co‐limited by B12 and PO4